2017
DOI: 10.1186/s13073-017-0484-3
|View full text |Cite
|
Sign up to set email alerts
|

Actionable gene-based classification toward precision medicine in gastric cancer

Abstract: BackgroundIntertumoral heterogeneity represents a significant hurdle to identifying optimized targeted therapies in gastric cancer (GC). To realize precision medicine for GC patients, an actionable gene alteration-based molecular classification that directly associates GCs with targeted therapies is needed.MethodsA total of 207 Japanese patients with GC were included in this study. Formalin-fixed, paraffin-embedded (FFPE) tumor tissues were obtained from surgical or biopsy specimens and were subjected to DNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 50 publications
9
62
0
Order By: Relevance
“…Recent genomic analyses have highlighted the genetic heterogeneity present in esophageal, esophago-gastric [10], and gastric cancer [11,12] as an underlying cause for the differences in outcome and heterogeneity of response to therapy. Quality of life also remains poor for many patients post-surgery, taking up to 3 years to return to pre-therapy levels in patients undergoing esophageal resection [13].…”
Section: The Need For Better Patient Stratificationmentioning
confidence: 99%
“…Recent genomic analyses have highlighted the genetic heterogeneity present in esophageal, esophago-gastric [10], and gastric cancer [11,12] as an underlying cause for the differences in outcome and heterogeneity of response to therapy. Quality of life also remains poor for many patients post-surgery, taking up to 3 years to return to pre-therapy levels in patients undergoing esophageal resection [13].…”
Section: The Need For Better Patient Stratificationmentioning
confidence: 99%
“…Indeed, we found that 7 of 53 (13%) Japanese TNBC patients had possible germline BRCA1/2 alterations by additional bioinformatic analysis of solid tumor sequencing. Comprehensive genomic analysis utilizing gene panel tests revealed the frequency of BRCA1 and BRCA2 alterations to be 3.9% and 10.6% in Japanese gastric cancers, respectively . Among them, we confirmed 3 patients with germline mutations and a family history, which indicates that BRCA1/2 germline mutations can be a cause of gastric cancer in Japan .…”
Section: Dna Double‐strand Break Repair Pathwaysmentioning
confidence: 64%
“…Among them, we found 11 patients with MSI, and 2 patients with polymerase ε mutation, which is another cause of hypermutation . We also identified 32 out of 207 (15.5%) Japanese gastric cancer patients as having hypermutated tumors, which were observed to be not only an MSI subtype, but also Epstein‐Barr virus infection, which is detectable by integrative genomic analysis that makes use of NGS technologies, chromosomal instability, and genomically stable subtypes of TCGA . In contrast, MSI is merely observed in breast cancer.…”
Section: Microsatellite Instability and Hypermutationmentioning
confidence: 87%
“…However, TMIT IV and TMIT I, the CD8 High groups, were enriched with mutations of BRCA2 and FLT4. BRCA2 is well‐known for its role in the repair of double stranded DNA breaks via homologous recombination (HR), and is also one of the actionable genes in GCs; defective BRCA2 implies a favorable response to platinum‐based chemotherapy and poly(ADP‐ribose) polymerase inhibitors . The association between BRCA2 mutation and TMIT I/IV, the highly inflamed TME groups, suggests that these subgroups of GC would be the good candidates for such treatment strategies.…”
Section: Discussionmentioning
confidence: 99%